Parents' Emotion Management for Personal Well-Being When Challenged by Their Online Work and Their Children's Online School - Henter, Ramona; Nastasa, Laura Elena (Frontiers in Psychology, 2021)
Parents’ emotion management was highly required during the lockdown caused by the COVID-19 pandemic as juggling with their own job moved online and with being a parent of a child whose school was online proved to be a challenge for many. Our sample was restricted to parents who had to work online from their homes while their children had to attend school online, as external imposed conditions. The present study was based on Mayer and Salovey’ theory and we aimed to investigate the relationship between the parents’ emotional intelligence and their ability to manage their emotions during this period, hypothesizing that a higher emotional intelligence and well developed emotion management abilities contribute to better adjustment to everyday challenges, thus contributing to keeping the level of exhaustion low. The double role played by these adults strained their resources, therefore we were also interested in their level of burnout after almost a year spent in a home turned into office and school. We also investigated the participants’ level of flourishing, as described by Ed Diener, as these changes impacted differently every parents’ wellbeing. The analysis of the data obtained offered us the possibility of issuing a series of recommendations for parents’ wellbeing in such a situation, as the prospect of continuing to work and learn online in future seems very real. The need to set clear boundaries between the roles played in these settings emerged as main objective of future therapeutic interventions based on positive psychology.